Development of high sensitive real-time PCR to detect mustard and other allergens of the family Brassicaceae in food samples - K. A. Kurbakov; V. N. Zhulinkova; M. Yu. Minaev (Теория и практика переработки мяса)
Mustard is a commonly used condiment including in production of other food products. As mustard is an allergen, it is necessary to control its presence. The development of PCR test-systems for its detection is complicated by the fact that this condiment can be made from seeds of various plant species (Brassica juncea, Brassica nigra, Sinapis alba) of the family Brassicaceae that are not closely related. This family includes other plant species such as white cabbage (Brassica oleracea) and rapeseed (Brassica napus), which can cause the allergic reaction, although seldom. In this connection, many authors use primers specific to many species of this family, including to allergens, to detect mustard. In this work, we used the similar strategy. To increase sensitivity, primers for the mitochondrial COX gene were selected. To increase PCR stability in analysis of deeply processed products, primers were selected for a region with a length of 61 base pair. In the work, the specificity and sensitivity of the developed PCR method was confirmed. Analyses of different products, including those that underwent deep technological processing, were carried out with these primers. Also, primers were selected to detect white mustard (S. alba). When analyzing products on the presence of white mustard, charac‑ teristic regional preferences were demonstrated: this species is used in manufacturing products mainly in the UK and USA.